Introduction to the Special Issue "The 2019 Swiss National Elections". Issue 2 (2nd July 2022) - Giger, Nathalie; Traber, Denise; Tresch, Anke
Abstract: This Special Issue brings together a large variety of contributions dealing with the influence of issues and issue competition, the structure of attitudes towards immigration and international cooperation and a series of non‐policy factors such as campaign consultants and the rise of female representation in Switzerland. In this introduction we place the contributions in the broader framework of current debates in the international literature and stress the substantial and methodological innovations of the articles. Last, we offer some more general thoughts on almost 30 years of Swiss electoral research taking stock of the historical development. Zusammenfassung: Diese Sonderausgabe umfasst eine Vielzahl von Beiträgen, die sich mit dem Einfluss von Themen und Themenkonkurrenz, der Struktur von Einstellungen gegenüber Einwanderung und internationaler Zusammenarbeit sowie einer Reihe themenunabhängiger politischer Faktoren wie Wahlkampfberatern und dem Anstieg der Frauenquote in der Schweiz befassen. In dieser Einleitung ordnen wir die Beiträge in den breiteren Rahmen aktueller Debatten in der internationalen Literatur ein und betonen die inhaltlichen und methodischen Innovationen der Artikel. Schliesslich formulieren wir einige allgemeinere Überlegungen zu fast 30 Jahren Schweizer Wahlforschung und ziehen eine Bilanz der historischen Entwicklung. Résumé: Ce numéro spécial rassemble une grande variété de contributions traitant de l'influence des enjeux et de la concurrence entre enjeux, de la structure des attitudes envers l'immigration et la coopération internationale et d'une série de facteurs non liés aux enjeux tels que les consultants de campagne et l'augmentation de la représentation féminine en Suisse. Dans cette introduction, nous plaçons les contributions dans le cadre plus large des débats actuels de la littérature internationale et soulignons les innovations substantielles et méthodologiques des articles. Enfin, nous proposons quelques réflexions plus générales sur près de 30 ans de recherche électorale en Suisse et faisons le point sur l'évolution historique.